Silica powder for cosmetics, and cosmetic
Through the preparation of non -fixed silica particles, the problem of silicon powder in cosmetics is difficult to provide a moist touch, and the humidity and environmental friendship of cosmetics with silicon dioxide powder are realized.
Patent Information
- Application Number
- CN202380046578.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-19
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-28
AI Technical Summary
The silica powder used in existing cosmetics is difficult to provide a wet touch and is not friendly to the environment and the human body.
By preparing the unspley silicon particles, the average circularity is more than 0.75, and the degree of convergence of specific conditions, the difference between the static angle and the collapse angle, the dispersion, the surface area, and the adhesion of the shelter to form the Cosmetics with a moist touch of silica powder.
The moist touch effect of the silicon powder in cosmetics is realized, and the friendship of the environment and the human body is improved.
Smart Images

Figure BDA0005183933310000251 
Figure BDA0005183933310000271 
Figure BDA0005183933310000291
Abstract
Description
Technical Field
[0001] The present invention relates to silicon dioxide powder for cosmetics and cosmetics. Background Art
[0002] Very fine resin particles (microplastics) such as PMMA (methyl methacrylate) particles, nylon particles, silicone particles, and polyurethane particles are mixed into cosmetics to adjust the feel of use and affinity with the skin.
[0003] Microplastics are very fine, so it is difficult to remove them by sewage treatment plants. They flow into rivers, oceans, ponds, etc., and there are concerns about their impact on marine ecosystems. In addition, microplastics accumulate in fish and shellfish, and there are concerns about their impact on the human body through these. Therefore, as an alternative to resin particles for cosmetics, it is required to develop raw materials that are more friendly to the environment and the human body.
[0004] As environmentally and human-friendly raw materials, silica particles with silicon dioxide (SiO2) as the main component can be cited. For example, Patent Document 1 proposes a cosmetic that is blended with 3 to 70 weight % of monodisperse nonporous spherical silica obtained by dispersing porous silica gel in high-temperature gas and calcining it to make it non-porous.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 2921058 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Silica powder composed of silica particles has a strong dry touch, and the moist touch of powder composed of soft particles such as nylon particles and urethane particles is less likely to be obtained.
[0010] Therefore, an object of the present invention is to provide a silica powder for cosmetics which has a new texture different from that of conventional silica powders and can give a moist texture when blended into cosmetics.
[0011] Solutions for solving problems
[0012] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by making the silica powder satisfy specific conditions. Based on this, the present invention has been completed.
[0013] That is, the present invention relates to the following.
[0014] <1> A silica powder for cosmetics, which is a silica powder formed of amorphous silica particles.
[0015] The average circularity of the silica particles is 0.75 or more,
[0016] The silica powder satisfies at least one of the following conditions (1) to (3).
[0017] (1) Aggregation degree is more than 60%
[0018] (2) The difference between the angle of repose and the angle of collapse is less than 15 degrees
[0019] (3) Dispersion degree is less than 50%
[0020] <2> according to <1> The silica powder for cosmetics has a stress relaxation rate of 18% or less when a load of 50N is applied.
[0021] <3> according to <1> or <2> The silica powder for cosmetics has a shear adhesion of 2.0 kPa or more when a load of 50 N is applied.
[0022] <4> according to <1> ~ <3> The silica powder for cosmetics described in any one of the preceding claims has a specific surface area of less than 5 m 2 / g.
[0023] <5> according to <1> ~ <4> The silica powder for cosmetics according to any one of the preceding claims, wherein the 50% particle size (D 50 ) is 0.5~100μm,
[0024] The 90% particle size (D 90 ) relative to the 10% particle size (D 10 ) 90 / D 10 ) is 1.0~5.0.
[0025] <6> A cosmetic comprising <1> ~ <5> The silica powder for cosmetics described in any one of the above.
[0026] <7> according to <6> The cosmetic further comprises one or more silica powders other than the aforementioned silica powder for cosmetics.
[0027] Effects of the Invention
[0028] According to the present invention, a silica powder for cosmetics which can give a moist touch when mixed in cosmetics can be provided. Furthermore, a cosmetic containing such a silica powder for cosmetics can be provided. DETAILED DESCRIPTION
[0029] The present invention will be described below, but the present invention is not limited to the examples in the following description. In the present specification, "to" indicating a numerical range means that the numerical values described before and after it are included as the lower limit and the upper limit.
[0030] <Silica powder for cosmetics>
[0031] The cosmetic silica powder of the present embodiment is a silica powder composed of amorphous silica particles, the average circularity of the silica particles is 0.75 or more, and the silica powder satisfies at least one of the following conditions (1) to (3).
[0032] (1) Aggregation degree is more than 60%
[0033] (2) The difference between the angle of repose and the angle of collapse is less than 15 degrees
[0034] (3) Dispersion degree is less than 50%
[0035] Here, in this specification, "powder" is used as a term referring to an aggregate of individual particles. That is, silica powder refers to an aggregate of silica particles.
[0036] The silica particles constituting the cosmetic silica powder (hereinafter referred to as silica powder) of the present embodiment are amorphous. By making the silica particles amorphous, silica powder that can be used for cosmetic purposes can be provided. It should be noted that amorphous in this specification means that no diffraction peak indicating crystals can be confirmed by powder X-ray diffraction method.
[0037] The average circularity of the silica particles constituting the silica powder of the present embodiment is 0.75 or more. If the average circularity is 0.75 or more, the shape of the particles becomes close to a sphere, and therefore, the ductility of the cosmetic containing the silica powder when applied to the skin becomes good. The average circularity is preferably 0.80 or more, more preferably 0.85 or more, further preferably 0.90 or more, and particularly preferably 0.95 or more. The upper limit of the average circularity is not particularly limited, and is most preferably 1. The average circularity is, for example, 0.75 to 1.
[0038] It should be noted that the circularity can be calculated as follows: for an image obtained by a particle image analysis device (e.g., Morphologi4 manufactured by Malvern), the area and perimeter of the particle are calculated using the image analysis software attached to the device, and the calculation is performed by substituting the results into the following formula. The average circularity is the average value of 20 particles.
[0039] Circularity = circumference of a circle with equal projected area / circumference of a particle
[0040] Circumference of a circle with equal projected area: When observing a particle from directly above, find the area of the particle's projection on the plane below, and calculate the length of the outline of a circle with the same area.
[0041] Particle circumference: The length of the outline of the particle projected on the plane below when the particle is viewed from above.
[0042] The silica powder of the present embodiment satisfies at least one of the following conditions (1) to (3).
[0043] (1) Aggregation degree is more than 60%
[0044] (2) The difference between the angle of repose and the angle of collapse is less than 15 degrees
[0045] (3) Dispersion degree is less than 50%
[0046] The silica powder of the present embodiment has a soft and moist touch by satisfying at least any one of the above conditions (1) to (3). Therefore, when the silica powder is blended in a cosmetic, an excellent moist feel can be exhibited.
[0047] Here, if the aggregation degree of the silica powder of this embodiment is 60% or more (condition (1)), the interaction between the silica particles is large, and the adhesion of the particles to each other is improved, so that when it is spread on the skin, it is soft and has a moist touch. The aggregation degree is preferably 65% or more, more preferably 70% or more, further preferably 75% or more, and particularly preferably 80% or more. In addition, the upper limit of the aggregation degree is not particularly limited, and is preferably 100%. The aggregation degree is, for example, 60 to 100%.
[0048] The degree of aggregation can be measured using a powder tester (e.g., manufactured by Hosokawa Micron Corporation, Model PT-X). Specifically, on a vibration table of the powder tester, a sieve with a mesh size of 250 μm, a sieve with a mesh size of 150 μm, and a sieve with a mesh size of 75 μm are installed in order from the top, 2.0 g of powder is placed on the upper sieve (mesh size of 250 μm), and the mixture is vibrated at an amplitude of 1.0 mm for 90 seconds. The mass of the powder remaining on each sieve is measured, and the degree of aggregation is calculated based on the following formula.
[0049] Aggregation degree (%) = {(A+B×3 / 5+C×1 / 5) / 2}×100
[0050] A: The mass of the powder on the upper sieve, B: The mass of the powder on the middle sieve, C: The mass of the powder on the lower sieve
[0051] In addition, if the difference between the angle of repose and the angle of collapse of the silica powder of the present embodiment is 15 degrees or less (condition (2)), the interaction between the silica particles is large, so the adhesion is improved, and a soft and moist touch is obtained. The difference angle is preferably 14 degrees or less, more preferably 13 degrees or less, further preferably 12 degrees or less, particularly preferably 11 degrees or less, and most preferably 10 degrees or less. In addition, the difference angle is preferably 0 degrees or more, more preferably 0.5 degrees or more, and further preferably 1 degree or more. The difference angle is, for example, 0 to 15 degrees.
[0052] Here, the repose angle and the collapse angle are described.
[0053] The angle of repose refers to the angle between the slope of the cone-shaped mountain formed when powder is dropped from a funnel at a certain height and remains stable without spontaneously collapsing, and the horizontal plane.
[0054] The angle of repose of the silica powder of this embodiment is preferably 20 degrees or more. By making the angle of repose 20 degrees or more, the silica powder can be evenly spread when applied to the skin. The angle of repose is more preferably 22 degrees or more, further preferably 25 degrees or more, and particularly preferably 30 degrees or more. In addition, from the viewpoint of ease of spreading, the angle of repose is preferably 80 degrees or less, more preferably 75 degrees or less, and further preferably 70 degrees or less. The angle of repose is preferably 20 to 80 degrees.
[0055] The collapse angle refers to the angle between the generatrix of the cone and the horizontal plane when a predetermined impact is applied to the cone-shaped mountain formed in the measurement of the angle of repose and a part of the cone collapses.
[0056] The collapse angle of the silica powder of this embodiment is preferably 20 degrees or more. By making the collapse angle 20 degrees or more, the adhesion of the silica particles to each other is very high, and an excellent moist feeling is obtained. The collapse angle is more preferably 22 degrees or more, further preferably 25 degrees or more, and particularly preferably 30 degrees or more. In addition, the collapse angle is preferably 70 degrees or less, more preferably 65 degrees or less, and further preferably 60 degrees or less. The collapse angle is preferably 20 to 70 degrees.
[0057] The repose angle and collapse angle can be measured using a powder tester (for example, model PT-X manufactured by Hosokawa Micron Corporation).
[0058] Specifically, a measuring table with a diameter of 80 mm is set horizontally, and a sieve with a mesh size of 1.7 mm and a funnel (e.g., made of stainless steel, with an upper opening diameter of 70 mm, a lower opening diameter of 7 mm, an inclination angle of 63 degrees, and a height of 7.5 cm from the measuring table to the lower opening of the funnel) are set above the measuring table. After 250 mL of powder is gently placed into the sieve, the sieve is vibrated with an amplitude of 1.5 mm, and the powder is dropped onto the measuring table through the sieve and the funnel, so that the powder is accumulated into a conical shape. Next, the conical shape is photographed from the front side, and the angle between the generatrix of the cone and the horizontal plane is measured once as the angle of repose. The collapse angle is as follows: For the powder for which the angle of repose has been measured, the same impact is applied 3 times using the automatic shocker (shocker) attached to the device, and the conical shape of the sample is photographed from the front side, and the angle between the generatrix of the cone and the horizontal plane is measured once as the angle of repose.
[0059] In addition, the silica powder of the present embodiment has a dispersion of 50% or less (condition (3)), so that the interaction between the silica particles becomes greater, the adhesion is improved, and a moist touch is obtained. The dispersion is preferably 45% or less, more preferably 40% or less, further preferably 35% or less, and particularly preferably 30% or less. In addition, the dispersion of the silica powder is preferably 0% or more, more preferably 1% or more. The dispersion is, for example, 0 to 50%.
[0060] Here, the dispersion degree (%) refers to the ratio of the mass of the powder before falling to the mass of the powder that is scattered and does not fall on the measuring table when a certain amount of silica powder is dropped toward the measuring table. The dispersion degree (%) can be measured using a powder tester (e.g., model PT-X manufactured by Hosokawa Micron Corporation). Specifically, 10 g of powder is placed on the top of the dispersion degree measuring unit of the powder tester, and the powder is dropped onto a surface dish with a diameter of 100 mm, which is placed 60 cm below the dispersion degree measuring unit. The mass of the powder deposited on the surface dish is weighed, and the dispersion degree is calculated according to the following formula.
[0061] Dispersion degree (%) = {(mass of powder before falling (g) - mass of powder deposited on the watch glass (g)) / mass of powder before falling (g)} × 100
[0062] The silica powder of this embodiment may satisfy only one of the above conditions (1) to (3), any two of the above conditions (1) to (3), or all of the above conditions (1) to (3). Among these, it is preferred to satisfy all of the above conditions (1) to (3) from the viewpoint of improving the adhesion between the silica particles and further improving the moist feeling.
[0063] When only one or two of the above conditions (1) to (3) are satisfied, it is particularly preferred that the condition (1) is satisfied because the moist feeling improvement effect is most significantly exhibited.
[0064] (50% particle size (D 50 ))
[0065] The 50% particle size (D 50 ) is preferably 0.5 to 100 μm. The 50% particle size (D 50 ) is 0.5 μm or more, the secondary aggregation of the silica particles can be suppressed, and good dispersion in the cosmetic can be easily obtained. 50 It is more preferably 0.7 μm or more, further preferably 0.9 μm or more, and particularly preferably 1.0 μm or more.
[0066] In addition, D 50 When the particle size is 100 μm or less, the silica particles are not too large, and thus the feeling of use when mixed with cosmetics is improved. 50 It is more preferably 50 μm or less, further preferably 20 μm or less, and particularly preferably 15 μm or less.
[0067] The 90% particle size (D 90 ) relative to the 10% particle size (D 10 ) 90 / D 10 ) is preferably 1.0 to 5.0. The D 90 / D 10 When the amount is within the above range, the reduction of coarse particles and the increase in specific surface area due to fine particles are suppressed, so that a good touch is obtained when applied to the skin. 90 / D 10 More preferably, it is 4.5 or less, further preferably, it is 4.0 or less, and particularly preferably, it is 3.5 or less. 90 / D 10 It is more preferably 1.1 or more, further preferably 1.2 or more, and particularly preferably 1.5 or more.
[0068] It should be noted that the 10% particle size (D 10 )、50% particle size (D 50 ) and 90% particle size (D 90 ) can be calculated using a particle size distribution measuring device based on an electrical detection method (e.g. Multisizer 4e manufactured by Beckman Coulter).
[0069] (Shear Adhesion)
[0070] The silica powder of the present embodiment preferably has a shear adhesion of 2.0 kPa or more when a load of 50 N is applied.
[0071] The shear adhesion shows the adhesion of the silica particles to each other. The greater the shear adhesion, the stronger the adhesion, and the moist feeling when the silica powder is mixed with cosmetics is improved. By making the shear adhesion above 2.0 kPa, the moist feeling is strongly felt. The shear adhesion of the silica powder is more preferably above 2.2 kPa, further preferably above 2.4 kPa, and particularly preferably above 2.6 kPa. In addition, the shear adhesion is preferably below 5.0 kPa, more preferably below 4.5 kPa, and further preferably below 4.0 kPa. That is, the shear adhesion of the silica powder is preferably in the range of 2.0 to 5.0 kPa.
[0072] The shear adhesion is measured using a powder layer shear force measuring device (e.g., NS-S500 manufactured by Nano Seeds Corporation) under the following conditions in accordance with JIS Z 8835:2016, and a yield locus (YL) is obtained by plotting the shear stress (y-axis) corresponding to each vertical stress (x-axis). The shear adhesion is obtained from the intersection of YL and the y-axis.
[0073] Conditions: cell inner diameter 43 mm, indentation gap 0.2 mm, indentation speed 0.2 mm / sec, stress relaxation time 100 sec, shear speed 10 μm / sec, vertical load 50 N
[0074] (Stress relaxation rate)
[0075] The stress relaxation rate is the degree to which the silica particles are rearranged when the silica powder is compacted by a load. The smaller the stress relaxation rate, the greater the interaction between the silica particles. As a result, the adhesion between the silica particles is improved, and a moist feeling is obtained.
[0076] The silica powder of this embodiment preferably has a stress relaxation rate of 18% or less when a load of 50N is applied. If the stress relaxation rate is 18% or less, a moist touch feeling can be obtained sufficiently. The stress relaxation rate of the silica powder is more preferably 17% or less, further preferably 16% or less, and particularly preferably 15% or less. In addition, the lower limit of the stress relaxation rate is not particularly limited, but is preferably 1% or more, and more preferably 3% or more. That is, the stress relaxation rate of the silica powder is preferably in the range of 1 to 18%.
[0077] The stress relaxation rate can be measured using a powder layer shear force measuring device (for example, NS-S500 manufactured by Nano Seeds Corporation).
[0078] Specifically, the vertical load applied to the powder layer is set to 50N. The stress relaxation rate (%) relative to the vertical stress at the beginning of shear can be calculated using the following formula based on the maximum vertical load a on the upper surface of the powder layer during pre-compaction and the vertical load b on the upper surface of the powder layer after stress relaxation for 100 seconds.
[0079] Stress relaxation rate (%) = (1-b / a) × 100
[0080] (Static friction coefficient)
[0081] The silica powder of this embodiment preferably has a static friction coefficient of 0.50 or more. If the static friction coefficient is 0.50 or more, both the resistance and the moist touch when applying to the skin can be taken into account. The static friction coefficient is more preferably 0.51 or more, further preferably 0.53 or more, and particularly preferably 0.54 or more. In addition, from the viewpoint of suppressing the resistance at the beginning of application, the static friction coefficient is preferably 1.00 or less, more preferably 0.95 or less, and further preferably 0.90 or less. That is, the static friction coefficient of the silica powder is preferably in the range of 0.50 to 1.00.
[0082] It should be noted that the dynamic friction coefficient can be measured using a static / dynamic friction measuring machine (e.g., "TL201Tt" manufactured by TRINITY LAB). Specifically, the contact head is set to a simulated finger made of carbamate, the load is set to 30 gf, the scanning distance is set to 40 mm, the scanning speed is set to 10 mm / sec, the coating substrate is set to an artificial leather substrate (e.g., manufactured by IDEATEX JAPAN CO., LTD), and the coating amount of the silica powder is set to a bulk volume per unit area of 0.8 μL / cm 2 The friction coefficient was measured. The maximum value in the range of 0 msec to 1000 msec among the obtained friction coefficients was taken as the static friction coefficient.
[0083] (dynamic friction coefficient)
[0084] The dynamic friction coefficient of the silica powder of the present embodiment is preferably 0.30 or more. If the dynamic friction coefficient is 0.30 or more, it can be extended on the skin while maintaining a moist touch. The dynamic friction coefficient is more preferably 0.33 or more, further preferably 0.35 or more, and particularly preferably 0.36 or more. In addition, from the viewpoint of ease of extension, the dynamic friction coefficient is preferably 0.80 or less, more preferably 0.75 or less, and further preferably 0.70 or less. That is, the dynamic friction coefficient of the silica powder is preferably in the range of 0.30 to 0.80.
[0085] The static friction coefficient can be measured using the static / dynamic friction measuring machine described above. Specifically, the friction coefficient is measured in the same manner as described above, and the average value of the obtained friction coefficient in the range of 1000 msec to 4000 msec is taken as the dynamic friction coefficient.
[0086] (loose bulk density)
[0087] The loose bulk density of the silica powder of this embodiment is preferably 0.45 g / cm 3 Above and 0.85g / cm 3 The loose bulk density is the bulk density measured when the powder is lightly filled into a container. The lightly filled powder is in a state where there are many gaps between the particles. If the loose bulk density is within the above range, the interaction between the silica particles is large, so there are many gaps and the rate of change to the load becomes large, so it becomes easy to get a moist feeling. The loose bulk density is more preferably 0.47 g / cm 3 Above 0.83g / cm 3 Below, more preferably 0.49 g / cm 3 Above 0.81g / cm 3 Below, particularly preferably 0.51 g / cm 3 Above 0.79g / cm 3 the following.
[0088] (Tapped bulk density)
[0089] The tapped bulk density of the silica powder of this embodiment is preferably 1.0 g / cm 3 Above and 1.5g / cm 3 The tapped bulk density is the bulk density measured after a container lightly filled with powder is vibrated to fill the gaps between particles and then refilled. If the tapped bulk density is within the above range, the particles are said to be compacted. The tapped bulk density is more preferably 1.02 g / cm 3 Above and 1.40g / cm 3 Below, more preferably 1.04 g / cm 3 Above and 1.35g / cm 3 Below, particularly preferably 1.05 g / cm 3 Above and 1.30g / cm 3 the following.
[0090] The loose bulk density and the tapped bulk density can be measured using a powder tester (for example, model PT-X manufactured by Hosokawa Micron Corporation).
[0091] Specifically, the silica powder is gently poured into a special cup until it overflows from the mouth of the special cup. The surface of the powder overflowing from the special cup is cut off with an attached scraper, and the mass including the cup is measured. The mass of the cup measured in advance is subtracted from this value to obtain the mass of the silica powder, and the value obtained by dividing it by the internal volume of the cup is taken as the loose bulk density.
[0092] Next, the special cup is covered with a lid, set on the tapping holder of the powder tester, and then filled with silica powder. A protective cover is installed on the lid. Next, tap it 180 times. After the tapping is completed, the lid and protective cover are removed, and the surface of the special cup is cut off with an attached scraper to measure the mass including the cup. The mass of the cup measured in advance is subtracted from this value to obtain the mass of the silica powder, and the value obtained by dividing it by the internal volume of the cup is used as the tapped bulk density.
[0093] (Compression)
[0094] The degree of compression is the rate of reduction in volume of the powder from a state where no load is applied to the powder to a state where a set load is applied.
[0095] The silica powder of this embodiment preferably has a compression degree of 37% or more. If the compression degree is 37% or more, the silica powder is compacted by the load when applied to the skin, so that a moist touch can be felt. The compression degree is more preferably 38% or more, further preferably 39% or more, and particularly preferably 39.5% or more. In addition, the compression degree is preferably 70% or less, more preferably 65% or less, further preferably 60% or less, and particularly preferably 55% or less. That is, the compression degree of the silica powder is preferably in the range of 37 to 70%.
[0096] The degree of compression is determined according to the following formula using the values of the loose bulk density and the tapped bulk density.
[0097] Compression degree (%) = {(tapped bulk density - loose bulk density) / tapped bulk density} × 100
[0098] (Specific surface area)
[0099] The specific surface area of the silicon dioxide powder of the present embodiment determined by a nitrogen adsorption method is preferably less than 5 m 2 / g. If the specific surface area of silica powder is less than 5m 2 / g, the silanol groups of the silica particles are reduced, thereby improving the adhesion between the silica particles, and thus improving the moist touch when the silica powder is blended into cosmetics.
[0100] The smaller the specific surface area of the silica powder, the better the moist feeling can be given. Therefore, 4.5 μm is more preferred.2 / g or less, more preferably 4m 2 / g or less, particularly preferably 3m 2 / g or less, most preferably 2m 2 / g or less. In addition, the lower limit is not particularly limited, and the specific surface area is preferably 0.1m 2 That is, the specific surface area of the silica powder is preferably 0.1 m 2 / g or more and less than 5m 2 / g.
[0101] It should be noted that the specific surface area can be calculated using the BET theory after obtaining an adsorption isotherm using a nitrogen adsorption method.
[0102] (Kong Rong)
[0103] The pore volume of the silica powder of this embodiment is preferably less than 0.1 cm 3 / g. Here, the pore volume refers to the pore volume derived from pores with a pore diameter of 1 to 100 nm. The silica component is dissolved by calcination to reduce the porosity, thereby reducing the specific surface area. Therefore, the pore volume is preferably less than 0.1 cm 3 / g.
[0104] The pore volume of the silica powder is more preferably 0.08 cm 3 / g or less, more preferably 0.06cm 3 / g or less, particularly preferably 0.04cm 3 The lower limit of the pore volume of the silica powder is not particularly limited, but is preferably 0 cm 3 / g or more, more preferably 0.001cm 3 / g or more, more preferably 0.005cm 3 / g or more. That is, the pore volume of the silica powder is preferably 0cm 3 / g or more and less than 0.1cm 3 / g.
[0105] In addition, the pore volume can be calculated using the BJH method according to the nitrogen adsorption method.
[0106] (Particle Strength)
[0107] The silica powder of the present embodiment preferably has a particle strength of 10 MPa or more. When the particle strength is 10 MPa or more, the particles constituting the silica powder have a strength that is not easily disintegrated, and thus the texture of the cosmetic product becomes good.
[0108] The particle strength of the silica powder is more preferably 15 MPa or more, further preferably 20 MPa or more, particularly preferably 25 MPa or more, and the upper limit is not particularly limited.
[0109] The particle strength of silica powder can be measured using a micro compression tester (eg, MCT-510 manufactured by Shimadzu Corporation). In the present embodiment, the particle strength is determined by measuring the compression strength of 40 silica particles and determining the particle strength based on the average value.
[0110] (Sodium concentration)
[0111] The silicon dioxide powder of this embodiment may contain sodium at a concentration of 1 to 300 ppm. By containing sodium at a concentration within the above range, crystallization can be suppressed, and sintering at high temperature becomes possible. The sodium concentration is preferably 2 ppm or more, more preferably 3 ppm or more, and further preferably 10 ppm or more. In addition, the sodium concentration is preferably 200 ppm or less, more preferably less than 200 ppm, further preferably 150 ppm or less, particularly preferably 100 ppm or less, and most preferably 50 ppm or less.
[0112] The silica particles constituting the silica powder of the present embodiment may contain impurity elements other than sodium within a range that does not impair the effects of the present invention. Examples of other impurity elements include Mg, Ca, Al, Fe, and Ti.
[0113] The concentration of each other impurity element is preferably 500 ppm or less, more preferably 300 ppm or less, and further preferably 100 ppm or less.
[0114] The concentration of sodium and other impurity elements can be measured by adding perchloric acid and hydrofluoric acid to silicon dioxide powder and applying strong heat to remove silicon as the main component, and then measuring by inductively coupled plasma (ICP) emission spectrometry.
[0115] (Oil absorption)
[0116] The silica particles constituting the silica powder of the present embodiment are preferably non-porous particles. If the particles are porous, the oil absorption becomes large, and the adhesion between the silica particles decreases, thereby worrying that the moist touch will decrease. Specifically, the oil absorption of the silica powder is preferably 100 ml / 100 g or less, more preferably 70 ml / 100 g or less, and most preferably 50 ml / 100 g or less. The lower limit is not particularly limited, but it is substantially difficult to make the oil absorption less than 20 ml / 100 g.
[0117] The oil absorption is preferably measured in accordance with JIS K5101-13-2:2004 using boiled linseed oil.
[0118] <Method for producing silica powder for cosmetics>
[0119] The silica powder of the present embodiment is obtained by, for example, forming a spherical silica precursor and heat-treating the silica precursor.
[0120] The silica precursor may be obtained by production, or a commercially available product may be used. Examples of the method for producing the silica precursor include a wet method and a granulation method.
[0121] The wet method refers to a method including a process of using a liquid substance as a silica source and gelling it to obtain a raw material of spherical silica particles. The granulation method is a method of using silica particles and forming them into a sphere with a binder, etc. Among these, by using a wet method that can control the particle size distribution and form spherical particles, spherical silica particles can be formed, so there is no need to adjust the shape of the particles by crushing, etc., and as a result, particles with a small specific surface area are obtained. In addition, the wet method is not easy to generate particles that are significantly smaller than the average particle size, and the specific surface area tends to become smaller after firing. In addition, in the wet method, by adjusting the impurities in the silica source, the amount of impurity elements such as titanium can be adjusted, and then the state in which the impurity elements are uniformly dispersed in the particles can be formed.
[0122] As a wet method, for example, a spray method, an emulsion / gelation method, etc. can be cited. As an emulsion / gelation method, for example, a dispersed phase containing a silica precursor is emulsified with a continuous phase, and the obtained emulsion is gelled to obtain a spherical silica precursor. As an emulsification method, it is preferred that a dispersed phase containing a silica precursor is supplied to a continuous phase by means of a microporous portion or a porous membrane to prepare an emulsion. Thus, an emulsion with a uniform droplet diameter is prepared, and as a result, a silica powder formed by silica particles of uniform particle size is obtained. Here, by adjusting the stirring speed during emulsification, the particle size of the silica particles can be adjusted.
[0123] As such an emulsification method, a micro-mixer method or a membrane emulsification method can be used. For example, the micro-mixer method is disclosed in International Publication No. 2013 / 062105.
[0124] The silica precursor obtained by the wet method is preferably porous. When the silica precursor is fired to obtain silica particles by a porous silica precursor, it is easier to obtain the shape of the silica particles, the particle size distribution of the powder, etc., compared with the silica particles produced by firing the non-porous raw material that is crushed. In addition, for the porous silica precursor, the primary particles of several nm to several 10 nm that constitute the internal pore structure are melted by heating, the surface area is reduced, and the pores are gradually buried. It is also known that if sodium is present, the melting point decreases.
[0125] Here, the silica precursor being porous means that pores are uniformly distributed in the silica precursor.
[0126] It is expected that the pore volume of the silica precursor obtained by the wet method is 0.05 to 2.2 ml / g. If the pore volume of the silica precursor is 0.05 ml / g or more, the silica particles will fully shrink during calcination, and the specific surface area can be reduced. In addition, if the pore volume of the silica precursor is 2.2 ml / g or less, the input bulk density before calcination is suppressed from becoming excessively large, and productivity can be improved. The pore volume of the silica precursor is more preferably 0.1 to 2.2 ml / g, more preferably 0.3 to 2.2 ml / g, further preferably 0.3 to 1.8 ml / g, particularly preferably 0.6 to 1.8 ml / g, and most preferably 0.7 to 1.5 ml / g.
[0127] The pore volume can be measured by the same method as above.
[0128] It is expected that the ignition loss of the silica precursor obtained by the wet method is 5.0 to 15.0 mass%. The ignition loss is the sum of the attached water attached to the silica precursor and the water produced by the condensation of the silanol groups contained in the silica precursor. By making the silica precursor have a moderate silanol group, the condensation is promoted during firing, and the silanol group becomes easy to reduce. The silanol group is reduced, so that the silica particles are charged, and the interaction between the silica particles increases. If the ignition loss is too much, there is a concern that the yield during firing is reduced and the productivity is deteriorated. Therefore, the ignition loss of the silica precursor is preferably 15.0 mass% or less, more preferably 13.0 mass% or less, and most preferably 12.0 mass% or less. If the ignition loss is too little, the silanol group becomes easy to remain during firing, so the ignition loss of the silica precursor is preferably 5.0 mass% or more, more preferably 6.0 mass% or more, and most preferably 7.0 mass% or more.
[0129] Here, the ignition loss is determined as the mass loss when 1 g of the silica precursor is heat-dried at 850° C. for 0.5 hours in accordance with JIS K 0067 (1992).
[0130] The average pore size of the silica precursor obtained by the wet method is preferably 1.0 to 50.0 nm. If the average pore size is 1.0 nm or more, the silica particles can be homogeneously non-porous until the inside. If the average pore size is 50.0 nm or less, the silica particles can be densified (low specific surface area) by calcination without residual pores, thereby obtaining a moist touch. The average pore size is more preferably 2.0 to 40.0 nm, further preferably 3.0 to 30.0 nm, and particularly preferably 4.0 to 20.0 nm.
[0131] The average pore size is determined by a BET method based on a nitrogen adsorption method using a specific surface area / pore distribution measuring apparatus (for example, “BELSORP-miniII” manufactured by Microtrac BEL Corp., “TriStar II” manufactured by Micromeritics, etc.).
[0132] In addition, the silica precursor obtained by the wet method preferably has a mass reduction rate of 10% or less when dried at 230° C. for 12 hours. If the mass reduction rate is 10% or less, when the silica precursor is calcined in a state where the particles are in contact with each other, the particles are less likely to be sintered, and spherical silica particles are easily obtained.
[0133] The mass reduction rate is more preferably 9% or less, further preferably 8% or less, and particularly preferably 6% or less. It is desirable that there is no mass change even after drying at 230° C. for 12 hours, so the lower limit is not particularly limited.
[0134] If the water content of the obtained silica precursor is high and the mass reduction rate exceeds 10% when dried at 230°C for 12 hours, it is preferably dried until it becomes 10% or less. Examples of drying methods include spray drying, static drying in a dryer, and ventilation treatment with dry air.
[0135] As a means of heat treatment of the silica precursor, there is no particular limitation, and heat treatment based on standing, heat treatment based on a rotary furnace, heat treatment based on spray combustion, etc. can be cited. In the heat treatment based on standing, a static electric furnace, a roller kiln, a continuous furnace classified as a tunnel furnace, etc. can be used. In the heat treatment based on a rotary furnace, a horizontal rotary furnace (rotary kiln), a rotary tubular furnace, etc. can be used. Among these, from the viewpoint of the uniformity of firing, it is preferably fired by heat treatment using a continuous furnace or a rotary furnace. Here, by adjusting the temperature during the heat treatment, the aggregation degree, repose angle, collapse angle, dispersion, specific surface area, shear adhesion, stress relaxation rate, compressibility, friction coefficient, etc. of the silica powder can be adjusted.
[0136] The heat treatment temperature is preferably 700° C. or higher, more preferably 800° C. or higher, further preferably 900° C. or higher, and particularly preferably 1000° C. or higher. In addition, from the viewpoint of suppressing crystallization, the heat treatment temperature is preferably 1600° C. or lower, more preferably 1500° C. or lower, and further preferably 1400° C. or lower. That is, the heat treatment temperature is preferably 700° C. or higher and 1600° C. or lower.
[0137] The calcination time may be appropriately adjusted depending on the calcination apparatus and calcination time used, and is preferably carried out within a range of 0.5 to 50 hours, and more preferably 1 to 10 hours.
[0138] The atmosphere during firing can be an atmosphere containing oxygen or an atmosphere not containing oxygen. When the silica precursor is obtained by a wet method, organic substances such as emulsifiers are mostly used, and in most cases the organic substances remain in the silica precursor. When the silica precursor containing organic substances is fired, the organic substances are carbonized under the condition of less oxygen, thus becoming the cause of coloration. Therefore, when the silica precursor contains organic substances, it is preferably fired in an atmosphere containing oxygen, more preferably in an atmospheric atmosphere.
[0139] In addition, during firing, it is preferred to fire the silica precursor in a state where the particles are in contact with each other. By firing in a state where the particles are in contact with each other, firing can be performed in a small volume. Therefore, for example, compared with the case where the silica precursor is dispersed in a gas for firing, the temperature unevenness and time unevenness during firing are reduced, and silica particles of certain quality are obtained. In the spray combustion method in which the silica precursor is dispersed in a gas, even when the raw material powder is blown in from the center of the flame, the temperature difference caused by the difference in the gas temperature blown in at the same time, the dispersion state of the raw material, the temperature difference caused by the difference in the part passing through the flame, the time difference until passing through the flame, and the time until the cooling of the distribution of the airflow (flow velocity) in the accompanying device, all of these will cause fluctuations in the firing conditions. By firing the silica precursor in a state where its particles are in contact with each other, the firing conditions in each silica precursor are made uniform and a certain quality is maintained.
[0140] After calcination, the silica particles are sometimes weakly sintered to each other, so in this case, they can be crushed. For crushing, in order not to damage the effect of the present invention and to maintain the average circularity and specific surface area, it is preferably carried out in a manner that the average circularity of the particles is not less than 0.75. In addition, it is preferred that the specific surface area does not increase due to the crushing process. The substantial increase in the specific surface area by the crushing process means that a part of the silica particles is crushed, fine damage is generated on the surface, and fine powder is generated. The increase in the specific surface area leads to a decrease in the moist feeling when the silica powder is mixed with cosmetics, so it is not preferred.
[0141] The crushing can be performed using a crushing device such as a cyclone mill or a jet mill, or can be performed using a vibrating screen.
[0142] The silica particles obtained by calcination can be surface treated with a silane coupling agent. In this process, the silanol groups existing on the surface of the silica particles constituting the silica powder react with the silane coupling agent, the silanol groups on the surface are reduced, and the dispersibility in oil can also be improved.
[0143] The surface treatment conditions are not particularly limited, and general surface treatment conditions may be used, and a wet treatment method or a dry treatment method may be used. From the viewpoint of performing a uniform treatment, a wet treatment method is preferred.
[0144] Examples of the silane coupling agent used for the surface treatment include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, and organic silazane compounds, etc. These can be used alone or in combination of two or more.
[0145] Specific examples of the surface treatment agent include amino propyl methoxy silane, amino propyl triethoxy silane, ureido propyl triethoxy silane, N-phenyl amino propyl trimethoxy silane, N-2 (amino ethyl) amino propyl trimethoxy silane and other amino silane coupling agents, glycidyl propyl trimethoxy silane, glycidyl propyl triethoxy silane, glycidyl propyl methyl diethoxy silane, glycidyl butyl trimethoxy silane, (3,4-epoxycyclohexyl) ethyl trimethoxy silane and other epoxy silane coupling agents, mercapto propyl trimethoxy silane, mercapto propyl triethoxy silane and other mercapto silane coupling agents, methyl trimethoxy silane, vinyl trimethoxy silane, octadecyl trimethoxy silane and other epoxy silane coupling agents. Silane coupling agents such as trimethoxysilane, phenyltrimethoxysilane, methacryloxypropyltrimethoxysilane, imidazole silane, triazine silane, CF3(CF2)7CH2CH2Si(OCH3)3, CF3(CF2)7CH2CH2SiCl3, CF3(CF2)7CH2CH2Si(CH3)(OCH3)2, CF3(CF2)7CH2CH2Si(CH3)C12, CF3(CF2)5CH2CH2SiCl3, CF3(CF2)5CH2CH2Si(OCH3)3, CF3CH2CH2SiCl3, CF3CH2CH2Si(OCH3)3, C8F 17 SO2N(C3H7)CH2CH2CH2Si(OCH3)3, C7F 15 CONHCH2CH2CH2Si(OCH3)3、C8F 17 CO2CH2CH2CH2Si(OCH3)3、C8F 17 -O-CF(CF3)CF2-O-C3H6SiCl3, C3F7-O-(CF(CF3)CF2-O)2-CF(CF3)CONH-(CH2)3Si(OCH3)3 and other fluorine-containing silane coupling agents, hexamethyldisilazane, hexaphenyldisilazane, trisilazane, cyclotrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane and other organic silazane compounds, etc.
[0146] The amount of the silane coupling agent used is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and still more preferably 0.10 parts by mass or more, and is preferably 5 parts by mass or less, and more preferably 2 parts by mass or less, based on 100 parts by mass of the silica particles.
[0147] Examples of the method for treating with a silane coupling agent include a dry method of spraying the silane coupling agent onto silica particles, and a wet method of dispersing silica particles in a solvent and then adding the silane coupling agent to react.
[0148] It should be noted that whether the surface of the silica particles is treated with a silane coupling agent can be confirmed by detecting a peak generated by a substituent of the silane coupling agent by IR. In addition, the amount of the silane coupling agent attached can be measured based on the amount of carbon.
[0149] The silica powder is obtained as an aggregate of silica particles by the above method. It should be noted that the silica particles obtained by the above method are amorphous.
[0150] <Cosmetics>
[0151] The cosmetic of the present embodiment includes the silica powder for cosmetics of the present embodiment. As described above, when the silica powder for cosmetics of the present embodiment is blended in cosmetics, it can give a moist touch. Therefore, the cosmetic of the present embodiment gives a moist touch.
[0152] The content ratio of the silica powder for cosmetics according to this embodiment in the cosmetics according to this embodiment can be adjusted as appropriate.
[0153] The cosmetics of this embodiment may contain other ingredients that are generally used in cosmetics in addition to the silica powder for cosmetics of this embodiment. As other ingredients, for example, water, oil components, water-miscible organic solvents, UV absorbers, antioxidants, preservatives / antibacterial agents, fragrances, surfactants, thickeners, inorganic powders, acids, alkalis, sugars, etc. The content ratio of these other ingredients in the cosmetics of this embodiment can be appropriately adjusted according to the purpose of use.
[0154] In addition, the cosmetic of this embodiment may contain one or more silica powders other than the silica powder of this embodiment in addition to the silica powder of this embodiment. By containing silica powders other than the silica powder of this embodiment, the touch can be adjusted to be close to the touch of resin, that is, soft and moist.
[0155] The shape of the silica powder other than the silica powder of the present embodiment is preferably a spherical shape, a scaly shape, a plate shape, a spherical shape, or a crushed shape, and more preferably a spherical shape.
[0156] The cosmetic of this embodiment can be in any appropriate form depending on the formulation and purpose, and examples of such form include powder, liquid, cream, gel, gel, and stick.
[0157] Examples of the cosmetics of this embodiment include makeup base, foundation, makeup cream, sunscreen, lotion, emulsion, beauty serum, facial mask, facial cleanser, eye shadow, lipstick, lip balm, deodorant, antiperspirant, and water-based gel.
[0158] Example
[0159] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited thereto. In the following description, common components are the same.
[0160] Examples 1 to 6 are embodiments, Examples 7 to 9 are comparative examples, and Example 10 is a reference example.
[0161] (Example 1)
[0162] As the dispersed phase, 30 g of No. 3 sodium silicate (manufactured by AGC SI-TECH CO., LTD., sodium silicate aqueous solution, SiO2 / Na2O (molar ratio) = 3, SiO2 concentration = 24 mass %) was used.
[0163] As the continuous phase, a mixture of n-decane (manufactured by Tosoh Corporation, HC-250, C 10 H 22 ) in which 0.7 mass % of sorbitan monooleate (manufactured by Sanyo Chemical Co., Ltd., IONET S80) as a surfactant was previously dissolved. 150 g.
[0164] While stirring n-decane with a surfactant as a continuous phase in a homogenizer (manufactured by Microtec Nition Co., Ltd., Physcotron, generator shaft NS-30UG / 20P), No. 3 sodium silicate as a dispersed phase was added and emulsified at 13,000 rpm for 5 minutes.
[0165] While the obtained emulsion was stirred by a three-in-one motor, carbon dioxide gas was blown into it at a rate of 0.4 L / min for 20 minutes to precipitate silica.
[0166] After that, the oil phase was removed, and the obtained aqueous phase containing silica gel was stirred at room temperature while sulfuric acid was added until the pH became 2, and then stirred at 80°C for 1 hour to remove the residual decane. For the purpose of adjusting the amount of sodium (Na), the slurry after the removal of the residual solvent was passed through 40 ml / g-SiO2 of acidic desalted water adjusted to pH 1 with sulfuric acid, filtered and washed, and then filtered and washed with desalted water heated to 80°C until the pH of the washing liquid became 5 or more. The obtained slurry was dried in a spray dryer (Nippon BUCHI KK, micro spray dryer B290) to obtain a silica precursor.
[0167] The obtained silica precursor was placed in an alumina crucible and heated at 1200°C for 1 hour in an electric furnace. It should be noted that in order to grasp the thermal history during the heating treatment, a Referthermo (which is formed from ceramic powder and therefore shrinks with good accuracy according to the thermal history) was installed in the same electric furnace. The indicated temperature of the Referthermo was 1200°C.
[0168] The heat-treated silica particles were cooled to room temperature, and the coarsely aggregated silica particles were crushed using a stainless steel sieve with a mesh size of 150 μm and a rubber scraper while the undersize was recovered to obtain silica powder of Example 1 which was an aggregate of silica particles.
[0169] (Example 2)
[0170] A silica powder was obtained by the same operation as in Example 1 except that the rotation speed of the homogenizer was changed to 10000 rpm.
[0171] (Example 3)
[0172] A silica powder was obtained by the same operation as in Example 1 except that the rotation speed of the homogenizer was changed to 5000 rpm.
[0173] (Example 4)
[0174] Silica powder was obtained by the same operation as in Example 1 except that the heat treatment temperature was changed to 1165°C.
[0175] (Example 5)
[0176] Silica powder was obtained by the same operation as in Example 1 except that the heat treatment temperature was changed to 1090°C.
[0177] (Example 6)
[0178] The silica powder obtained in Example 1 was mixed with other silica powder (Sunsphere NP-30 manufactured by AGC SI-TECH CO., LTD.) at a mass ratio of 1:1 to obtain silica powder.
[0179] (Example 7)
[0180] As silica powder, Sunsphere NP-20 manufactured by AGC SI-TECH CO., LTD. was prepared.
[0181] (Example 8)
[0182] As silica powder, Sunsphere NP-30 manufactured by AGC SI-TECH CO., LTD. was prepared.
[0183] (Example 9)
[0184] As silica powder, Sunsphere NP-100 manufactured by AGC SI-TECH CO., LTD. was prepared.
[0185] (Example 10)
[0186] As nylon powder, Orgasol 2002EXD NAT COS manufactured by Arkema Corporation was prepared.
[0187] Powder X-ray diffraction measurement was performed on the silica powders of Examples 1 to 9. As a result, it was found that all of them were composed of amorphous silica particles.
[0188] The following measurements were performed on the silica powders of Examples 1 to 9 and the nylon powder of Example 10. The results are shown in Table 1.
[0189] <Average roundness of particles>
[0190] The powder was photographed using a scanning electron microscope (JCM-7000 manufactured by JEOL Ltd.), and the area and perimeter of the particles were obtained using image analysis software (image analysis software included with the particle image analysis device "Morphologi4" manufactured by Malvern Co.), and the results were substituted into the following formula. The average circularity of 20 particles was obtained and taken as the average circularity.
[0191] Circularity = circumference of a circle with equal projected area / circumference of a particle
[0192] Circumference of a circle with equal projected area: When observing a particle from directly above, find the area of the particle's projection on the plane below, and calculate the length of the outline of a circle with the same area.
[0193] Particle circumference: The length of the outline of the particle projected on the plane below when the particle is viewed from above.
[0194] <50% particle size of powder (D 50 )、90% particle size (D 90 ) relative to the 10% particle size (D 10 ) 90 / D 10 )>
[0195] After adding distilled water to the powder to form a 0.05 mass % slurry, the powder was treated with an ultrasonic cleaner at a frequency of 45 kHz for 2 minutes, and the 50% particle size (D ) in the cumulative particle size distribution based on the volume standard was calculated using a particle size distribution measuring device using an electrical detection method (Multisizer 4e manufactured by Beckman Coulter). 50 )(Settings: pore size 50 μm, effective N number 50000, current 800 μA, gain 4, stirring speed 15, electrolyte ISOTON).
[0196] In addition, the 90% particle size (D 90 ) and 10% particle size (D 10 ), calculate D from the obtained value 90 Relative to D 10 The ratio (D 90 / D 10 ).
[0197] <Specific surface area of powder>
[0198] The powder was dried under reduced pressure at 230°C to completely remove moisture to prepare a sample. The specific surface area of the sample was determined by the multipoint BET method using nitrogen gas in an automatic specific surface area / pore distribution measuring apparatus "TriStar II" manufactured by Micromeritics.
[0199] <Shear adhesion of powder>
[0200] The yield locus (YL) was plotted against the shear stress (y-axis) corresponding to each vertical stress (x-axis) using a powder layer shear force measuring device (manufactured by Nano Seeds Corporation, NS-S500) under the following conditions according to JIS Z8835:2016. The shear adhesion was determined from the intersection of YL and the y-axis.
[0201] Conditions: cell inner diameter 43 mm, indentation gap 0.2 mm, indentation speed 0.2 mm / sec, stress relaxation time 100 sec, shear speed 10 μm / sec, vertical load 50 N
[0202] <Stress relaxation rate of powder>
[0203] A powder layer shear force measuring device (manufactured by Nano Seeds Corporation, model NS-S500) was used to apply a vertical load of 50 N to the powder layer. The stress relaxation rate (%) relative to the vertical stress at the start of shear was calculated using the following formula based on the maximum vertical load a on the upper surface of the powder layer during pre-compression and the vertical load b on the upper surface of the powder layer after stress relaxation for 100 seconds.
[0204] Stress relaxation rate (%) = (1-b / a) × 100
[0205] <Loose bulk density, tapped bulk density, aggregation, angle of repose, angle of collapse, difference angle and dispersion of powders>
[0206] The measurement was carried out using a powder tester (model: PT-X) manufactured by Hosokawa Micron Corporation.
[0207] (loose bulk density)
[0208] Gently pour the powder into a special cup with an internal volume of 100 mL, filling it until the powder overflows from the cup. Use the attached scraper to cut off the powder overflowing from the cup, and measure the mass including the mass of the cup. Subtract the mass of the cup measured in advance from this value to find the mass of the powder, and divide it by the internal volume of the above cup to calculate the loose bulk density.
[0209] (Tapped bulk density)
[0210] After measuring the loose bulk density, the above-mentioned special cup is covered with a lid, set on the tapping holder of the powder tester, further filled with powder, and a protective cover is installed on the lid. Then, it is tapped 180 times. After the tapping is completed, the lid and protective cover are removed, and the surface part of the cup is cut off with an attached scraper, and the mass including the above-mentioned cup is measured. The mass of the cup measured in advance is subtracted from this value to obtain the mass of the silica powder, which is divided by the internal volume of the above-mentioned cup to calculate the tapped bulk density.
[0211] (Compression)
[0212] The compression degree is determined from the values of the tapped bulk density and the loose bulk density according to the following formula: Compression degree (%) = {(tapped bulk density - loose bulk density) / tapped bulk density} × 100
[0213] (Agglomeration)
[0214] On the vibration table of the powder tester, install a sieve with a mesh size of 250 μm, a sieve with a mesh size of 150 μm, and a sieve with a mesh size of 75 μm in order from the top, place 2.0 g of powder on the upper sieve (mesh size of 250 μm), vibrate with an amplitude of 1.0 mm for 90 seconds, measure the mass of the powder remaining on each sieve, and calculate the degree of aggregation based on the following formula.
[0215] Aggregation degree (%) = {(A+B×3 / 5+C×1 / 5) / 2}×100
[0216] A: The mass of the powder on the upper sieve, B: The mass of the powder on the middle sieve, C: The mass of the powder on the lower sieve
[0217] (angle of repose)
[0218] The measuring platform of diameter 80mm is set horizontally, and the sieve and funnel of mesh 1.7mm (stainless steel, upper opening diameter 70mm, lower opening diameter 7mm, inclination angle 63 degrees, the height of the lower opening portion from the measuring platform to the funnel is 7.5cm) are set above the measuring platform. After 250mL of powder is gently put into the sieve, the sieve is vibrated with an amplitude of 1.5mm, and falls onto the measuring platform by the sieve and the funnel, so that the powder is deposited into a cone shape. Then, the cone shape is photographed from the positive side, and the angle between the generatrix of the cone and the horizontal plane is measured. The number mean of 1 measurement is used as the angle of repose.
[0219] (Crash Angle)
[0220] For the powder whose repose angle is measured, the same impact is applied three times by the automatic impactor attached to the device, and the cone shape of the sample is photographed from the front side, and the angle between the generatrix of the cone and the horizontal plane is measured. The number average of the measurements is taken as the collapse angle.
[0221] (Difference angle)
[0222] Calculate the difference between the angle of repose and the angle of collapse.
[0223] (Dispersion)
[0224] 10 g of powder was placed on the top of the dispersion measuring cell and dropped onto a 100 mm diameter watch glass placed 60 cm below the dispersion measuring cell. The dispersion (%) was calculated from the mass of the powder deposited on the watch glass using the following formula.
[0225] Dispersion degree (%) = {(mass of powder before falling (g) - mass of powder deposited on the watch glass (g)) / mass of powder before falling (g)} × 100
[0226] <Evaluation of friction characteristics of powder>
[0227] (Static friction coefficient)
[0228] A static / dynamic friction measuring machine (manufactured by TRINITY LAB, TL201Tt model) was used, with the contact head set to a simulated finger made of urethane, the load set to 30 gf, the scanning distance set to 40 mm, the scanning speed set to 10 mm / sec, and the coating substrate set to an artificial leather substrate (manufactured by IDEATEX JAPAN CO., LTD). The coating amount of the powder was set to a loose volume per unit area of 0.8 μL / cm 2 The friction coefficient was measured. The maximum value in the range of 0 msec to 1000 msec among the obtained friction coefficients was taken as the static friction coefficient.
[0229] (dynamic friction coefficient)
[0230] The friction coefficient was measured by the same method as above using a static / dynamic friction measuring machine (manufactured by TRINITY LAB, Model TL201Tt), and the average value of the obtained friction coefficient in the range of 1000 msec to 4000 msec was taken as the dynamic friction coefficient.
[0231] <Touch evaluation>
[0232] (Powder: Examples 1 to 10)
[0233] The touch of the powders of Examples 1 to 10 obtained above was sensory evaluated by five panelists in the following procedure. The evaluation results are shown in Table 1.
[0234] (step)
[0235] Take an appropriate amount (about one spoonful of micro-spoon) of powder on the back of your hand or the inside of your forearm and spread it evenly with your fingers. At this time, evaluate the "moist feeling" and "softness" according to the following criteria. Calculate the average score of each item and evaluate the touch.
[0236] 〔Wet feeling〕
[0237] 5 points: moist
[0238] 1 point: Dry
[0239] 〔Softness〕
[0240] 5 points: soft
[0241] 1 point: hard
[0242] [Table 1]
[0243]
[0244] According to the results shown in Table 1, the silica powders of Examples 1 to 6 as Examples showed excellent moist feeling and soft touch compared with the comparative examples. On the other hand, the silica powders of Examples 7 to 9 as comparative examples had an aggregation degree of less than 60%, a difference between the angle of repose and the angle of collapse of more than 15 degrees, and a dispersion degree of more than 50%, and therefore had poor touch in terms of moist feeling and softness.
[0245] <Cosmetics>
[0246] (Powder foundation: Examples 11 to 18)
[0247] According to the composition described in Table 2 below, a powder foundation was prepared.
[0248] (Manufacturing method)
[0249] 1) Group A was weighed and mixed three times within 30 seconds in a Henschel mixer (manufactured by HANIL ELECTRIC CO., LTD., Hanil mixer, model LM-110T) so as to be uniform.
[0250] 2) Weigh Group B and mix evenly with a spatula.
[0251] 3) Group B was added to the mixed and homogenized Group A, and mixed three times within 30 seconds in a Henschel mixer so as to be homogenized, thereby obtaining a powder foundation.
[0252] [Table 2]
[0253]
[0254] (※1) to (※8) in Table 2 are as follows.
[0255] (※1) Mg stearate treated talc: MST-1TALC SX (Daito Chemical Industry Co., Ltd.)
[0256] (※2) Mica treated with magnesium stearate: MST-2SERICITE S (Daito Chemical Industry Co., Ltd.)
[0257] (※3) Mg stearate treated titanium dioxide: MST-1TiO2 R250 (Daito Chemical Industry Co., Ltd.)
[0258] (※4) Yellow Iron Oxide: SunPURO Yellow Iron Oxide: (SUNCHEMICAL)
[0259] (※5) Red Iron Oxide: SunPURO Red Iron Oxide
[0260] (※6) Black iron oxide: SunPURO Red Iron Oxide
[0261] (※7) Mixture of diheptyl succinate, (caprylyl glyceryl / sebacic acid) copolymer
[0262] (※8) A mixture of ethylhexylglycerin and caprylic glyceryl: NIKKOGUARD
[0263] The texture of each powder foundation obtained above was sensory evaluated by five panelists according to the following procedure.
[0264] 〔step〕
[0265] Take an appropriate amount (about one spoonful of a micro-spoon) of powder foundation on the back of your hand or the inside of your forearm and spread it evenly with your fingers. At this time, evaluate the "moist feeling", "softness" and "good ductility" according to the following criteria. Calculate the average score of each item and evaluate the touch.
[0266] 〔Wet feeling〕
[0267] 5 points: moist
[0268] 1 point: Dry
[0269] 〔Softness〕
[0270] 5 points: soft
[0271] 1 point: hard
[0272] Regarding "moist feeling", "softness" and "good spreadability", the powder foundations of Examples 11 to 14 had a touch feeling closer to that of the powder foundation of Example 18 than those of Examples 15 to 17.
[0273] In order to impart the same effect, the silica powder of this embodiment can also be blended into other preparations (including emulsified preparations), such as compressed foundation, rouge (eye shadow, blush), face powder, highlighters, eyebrow pencils, dry shampoo, body wash, powdered deodorants, etc.
[0274] (Aqueous gel: Examples 19 to 21)
[0275] According to the composition described in Table 3 below, an aqueous gel was prepared.
[0276] (Manufacturing method)
[0277] 1) The previously dispersed group B is added to the group A and stirred until the mixture becomes uniform to obtain a first composition.
[0278] 2) While stirring the first composition, add the aqueous solution of group C and continue stirring until the mixture becomes uniform to obtain a second composition.
[0279] 3) Group D is added to the second composition and stirred until the mixture becomes uniform to obtain a third composition.
[0280] 4) Water or silica dispersion of group E is added to the third composition and stirred until it becomes uniform to obtain an aqueous gel.
[0281] [Table 3]
[0282] Table 3 (Compound Amount: Mass %)
[0283]
[0284] (※1) to (※4) in Table 3 are as follows.
[0285] (※1) Propylene glycol: ZEMEA Select Propylene glycol (DuPont Tate & Lyle Bio Products)
[0286] (※2) Carbomer: Carbopol Ultrez 10polymer (Lubrizol)
[0287] (※3) Potassium hydroxide: Potassium hydroxide (Kanto Chemical Co., Ltd.)
[0288] (※4) Phenoxyethanol: Phenoxyethanol-S (Yokaichi Gosei Co., Ltd.)
[0289] The aqueous gels of Examples 19 to 21 obtained above were subjected to sensory evaluation by one evaluator according to the following procedure.
[0290] 〔step〕
[0291] Take an appropriate amount (about one micro-spoon) of the water-based gel onto the back of your hand and spread it evenly with your fingertips.
[0292] Sensory evaluation was performed, and as a result, Example 20 provided a good touch compared with Examples 19 and 21.
[0293] In order to impart the same effect, the silica powder of this embodiment can also be blended into other preparations (including emulsified preparations), such as lotions, beauty serums, facial masks, peel-off facial masks, pen-type eyeliners, eyebrow pencils, hair tonics, repellents, emulsions, gel creams, face creams, hand creams, body creams, sunscreens, makeup bases, foundations, concealers, mascara, cleansing milks, cleansing creams, rinse-off packs, enamel treatments, rinses, hair treatments, color treatments, hair styling agents, deodorants, and the like.
[0294] (Lipstick: Examples 22-24)
[0295] According to the composition described in Table 4 below, lipstick was prepared.
[0296] (Manufacturing method)
[0297] 1) Group A was weighed and stirred in a disperser while being heated at 120° C. until the mixture became uniform, thereby obtaining a first composition.
[0298] 2) Group B is added to the first composition, and the mixture is continuously stirred in a disperser until the mixture becomes uniform, thereby obtaining a second composition.
[0299] 3) Group C is added to the second composition and stirred until the mixture becomes uniform to obtain a third composition.
[0300] 4) The third composition was poured into a lipstick container, and allowed to stand at room temperature for 5 minutes and at -15°C for 15 minutes to obtain a lipstick.
[0301] [Table 4]
[0302]
[0303] (※1) to (※19) in Table 4 are as follows.
[0304] (※1) Diisostearyl Malate: COSMOL 222 (The Nisshin OilliO Group, Ltd.)
[0305] (※2) Hydrogenated polyisobutylene: PARLEAM 18 (NOF Corporation)
[0306] (※3) Paraffin wax: Paraffin Wax-125 (Nippon Seiro Co., Ltd.)
[0307] (※4) Alkyl benzoate (C12-15): CRODAMOL AB (Croda Japan KK)
[0308] (※5) Mixture of diheptyl succinate and (caprylyl glycerin / sebacic acid) copolymer: LexFeel N5 MB (INOLEX, INC.)
[0309] (※6) Octyldodecanol: Risonol 20SP (KOKYU ALCOHOL KOGYO CO.,LTD.)
[0310] (※7) Diisopropyl dilinoleate: KAK DADIP-R (KOKYU ALCOHOL KOGYO CO., LTD.)
[0311] (※8) Pentaerythritol tetraethylhexanoate: SALACOS 5408 (The Nisshin OilliO Group, Ltd.)
[0312] (※9) Pentaerythritol tetraisostearate: SALACOS 5418V (Nisshin OilliO Group, Ltd.)
[0313] (※10) Polyglyceryl-2-isostearate: COSMOL 41V (Nisshin OilliO Group, Ltd.)
[0314] (※11)Synthetic wax: Microease 114S (MICRO Powders, INC.)
[0315] (※12) Microcrystalline wax: MULTIWAX W-445 (Sonneborn LLC)
[0316] (※13) Propylparaben: MEKKINS-P(C) (Ueno Pharmaceutical Co., Ltd.)
[0317] (※14) Tocopherol: Tocopherol 100 (Nisshin OilliO Group, Ltd.)
[0318] (※15) White pigment paste (titanium oxide, polyglyceryl-2-triisostearate): DK-PGT PASTE Ti (Daito Chemical Industry Co., Ltd.)
[0319] (※16) Red pigment paste (polyglyceryl-2-triisostearate, Red 202): DK-PGT PASTE R7 (Daito Chemical Industry Co., Ltd.)
[0320] (※17) Red pigment paste (Red 226, polyglycerol-2-triisostearate): DK D&C RED No. 30 was dispersed in COSMOL 43V (Nisshin OilliO Group, Ltd.) using a triple roll mill (EXAKT, EXAKT Technologies, Inc.) to give a concentration of 30 wt%.
[0321] (※18) Yellow pigment paste (polyglycerol-2-triisostearate, Yellow 4): DK-PGT PASTE Y5L (Daito Chemical Industry Co., Ltd.)
[0322] (※19) Pearlescent pigment: Sunpuro Fine white (SunChemical Corporation)
[0323] The lipsticks of Examples 22 to 24 obtained above were subjected to sensory evaluation by one panelist according to the following procedure.
[0324] 〔step〕
[0325] The lipstick was applied to the lips and the spreadability was evaluated.
[0326] The results of the sensory evaluation are as follows: The lipstick spreadability of the lipsticks of Examples 22 and 23 is still good compared to 24.
[0327] In order to impart the same effect, the silica powder of this embodiment can also be blended into other solid oil-based preparations, such as foundation, concealer, lipstick, eyeliner, eyebrow pencil, stick deodorant, stick eye shadow, stick beauty serum, stick highlighter, makeup remover, hair styling agent, etc.
[0328] Various embodiments have been described above, but the present invention is certainly not limited to these examples. It is obvious to those skilled in the art that various variations or modifications can be thought of within the scope of the claims, and these also belong to the protection scope of the present invention. In addition, the various constituent elements in the above-mentioned embodiments can be combined arbitrarily within the scope of the gist of the invention.
[0329] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-095198) filed on June 13, 2022 and the Japanese patent application (Japanese Patent Application No. 2023-006655) filed on January 19, 2023, the contents of which are incorporated herein by reference.
Claims
1. A silica powder for cosmetics, which is a silica powder formed from amorphous silica particles, The average circularity of the silica particles is greater than 0.75, The silicon dioxide powder satisfies at least one of the following conditions (1) to (3), (1) The degree of aggregation is 60% or more, (2) The difference between the angle of repose and the angle of collapse is less than 15 degrees, (3) The degree of dispersion is 50% or less. 2 . The silica powder for cosmetics according to claim 1 , wherein the stress relaxation rate when a load of 50 N is applied is 18% or less. 3 . The silica powder for cosmetics according to claim 1 , which has a shear adhesion of 2.0 kPa or more when a load of 50 N is applied.
4. The silica powder for cosmetics according to claim 1 or 2, wherein the specific surface area is less than 5 m 2 / g.
5. The silica powder for cosmetics according to claim 1 or 2, wherein the 50% particle size (D 50 ) is 0.5~100μm, The 90% particle size (D 90 ) relative to the 10% particle size (D 10 ) 90 / D 10 ) is 1.0~5.
0.
6. A cosmetic comprising the silica powder for cosmetics according to claim 1 or 2. 7 . The cosmetic according to claim 6 , further comprising one or more silica powders other than the silica powder for cosmetics.
Citation Information
Patent Citations
Information processing apparatus
JP2022095198A
Production method of antibacterial twist yarn, and antibacterial twist yarn, antibacterial fabric and antibacterial tatami mat
JP2023006655A
Silica spherical body and affinity carrier
WO2013062105A1